2013
DOI: 10.1016/j.molcel.2013.07.023
|View full text |Cite
|
Sign up to set email alerts
|

FANCD2 Binds MCM Proteins and Controls Replisome Function upon Activation of S Phase Checkpoint Signaling

Abstract: Proteins disabled in Fanconi anemia (FA) are necessary for the maintenance of genome stability during cell proliferation. Upon replication stress signaling by ATR, the FA core complex monoubiquitinates FANCD2 and FANCI in order to activate DNA repair. Here, we identified FANCD2 and FANCI in a proteomic screen of replisome-associated factors bound to nascent DNA in response to replication arrest. We found that FANCD2 can interact directly with minichromosome maintenance (MCM) proteins. ATR signaling promoted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
226
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(240 citation statements)
references
References 56 publications
(70 reference statements)
12
226
1
1
Order By: Relevance
“…iPOND iPOND was performed as previously described [41,42]. PTEN +/+ and PTEN −/− HCT116 cells were labeled with 10 µM EdU for 15 min before 4 mM HU treatment for 5h.…”
Section: Chromatin Fractionmentioning
confidence: 99%
“…iPOND iPOND was performed as previously described [41,42]. PTEN +/+ and PTEN −/− HCT116 cells were labeled with 10 µM EdU for 15 min before 4 mM HU treatment for 5h.…”
Section: Chromatin Fractionmentioning
confidence: 99%
“…113 An unbiased proteomics screen of chromatinbound FANCD2 immune complexes revealed that FANCD2 physically associates with the minichromosome maintenance 2-7 (MCM2-MCM7) replicative helicases. 114,115 FANCD2 interacts with MCM2-MCM7 in response to ATR-mediated DNA replication stress signaling independently of the core FA complex and monoubiquitination. 115 In the absence of FANCD2, replication forks stall stochastically and primary cells exhibit increased senescence, indicating that FANCD2 is required for replication fork progression.…”
Section: Fancd2 and Fanci Functionmentioning
confidence: 99%
“…114,115 FANCD2 interacts with MCM2-MCM7 in response to ATR-mediated DNA replication stress signaling independently of the core FA complex and monoubiquitination. 115 In the absence of FANCD2, replication forks stall stochastically and primary cells exhibit increased senescence, indicating that FANCD2 is required for replication fork progression. 115 Schlacher and colleagues also showed that FANCD2 is necessary to protect stalled replication forks from MRE11-mediated degradation, and that fork protection in the absence of FANCD2 can be rescued by RAD51.…”
Section: Fancd2 and Fanci Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides its role in dealing with ICL, recent evidence has shown that the FA pathway might also be involved in safeguarding the integrity of replication forks. For instance, analysis of the composition of the replisome after treatment with hydroxyurea revealed the recruitment of FANCD2 through the interaction with phosphorylated MCM2, where it would slow down replication to allow fork stabilization [47]. FANCD2 has also been involved in the protection of reversed forks in cooperation with BRCA2 and Rad51 [34,48].…”
Section: Rs As a Fuel Of Tumorogenesismentioning
confidence: 99%